Estimation of wind power resources of a small domain with complicated topography - Osadchy, V.I.; Skrynyk, O.A.; D.O. Oshurok, D.O.; Skrynyk, O.Ya. (Reports of the National Academy of Sciences of Ukraine, 2017)
We have analyzed the capability of the meteorological preprocessor CALMET to estimate wind resources of a small domain with complicated topography. The efficacy of the methodology proposed has been tested by calculating the wind power of the Ternopil region for the period of 1981—2010.